THE SIGNIFICANCE OF GENDER EQUALITY IN EDUCATION AND SOCIETY DEVELOPMENT - Allambergenova B.K. (International Journal of Literature and Language Studies, 2026)
The article is devoted to the study of the relationship between education and gender equality. The article examines various factors influencing the achievement of equality between men and women in the education system, and also proposes prospective measures to eliminate gender barriers in the education sector. The author analyzes the historical aspects and current state of the problem of gender equality in education, highlights the role of women in this area and their equality, opportunities for accessing educational resources.